O controle jurisdicional nos concursos públicos - Machado Júnior, Agapito (2006)
When regarded as an instrument to achieve commonwealthy, the State amasses political power and the capacity to create and impose behaviour patterns to community, which are represented through three basic functions: legislative, administrative and jurisdictional. Political power comes from citizenry, being attributed to the State in order to achieve the wellbeing for the whole society. Under this democratic focus and aware that, as a juridical creation, there is no State, physically speaking, it’s coherent that citizenry itself executes and materializes the politic power credited to them. Only through a competitive examination the citizen is able to become a civil servant. The competitive examination is an administrative proceeding established in the Constitution according to which any citizen will be able to apply for and eventually take a position in the structure of civil service. The system of competitive examination is an instrument the State uses to assure democracy, equality, impersonality, morality and efficiency in Public Administration. As an administrative proceeding, whose requirements are indicated in legislation, competitive examinations are subject to the control of the Public Administration itself (self-control), as well of the Judicial Power as regards legality, being such control broadened in Social Democratic State